2007
DOI: 10.1016/j.nuclphysa.2007.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Total gluon shadowing due to fluctuation effects

Abstract: We show a new physical phenomenon expected for the ratio RpA of the unintegrated gluon distribution of a nucleus over the unintegrated gluon distribution of a proton scaled up by the atomic factor A 1/3 in the fluctuation-dominated (diffusive scaling) region at high energy. We calculate the dependence of RpA on the atomic number A, the rapidity Y and the transverse gluon momentum k ⊥ . We find that RpA exhibits an increasing gluon shadowing with growing rapidity, approaching 1/A 1/3 at asymptotic rapidities wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…The ratio of the gluon distribution in a nucleus to the same quantity in a proton was computed in Ref. [131].…”
Section: Diffusive Scalingmentioning
confidence: 99%
“…The ratio of the gluon distribution in a nucleus to the same quantity in a proton was computed in Ref. [131].…”
Section: Diffusive Scalingmentioning
confidence: 99%
“…). At high energy, such that σ 2 ≫ 1, it has been shown that fluctuations do strongly modify measurable quantities [13,14]. (A more detailed presentation of the recent theoretical progress is given in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…(12) A solution to the evolution equations, which is not yet available because of their complexity, would have helped to better understand the subasymptotics. However, using the methods outlined in the previous subsections, phenomenological consequences of fluctuations in the fixed coupling case have been studied, for example for DIS and diffractive cross sections [9], forward gluon production in hadron-hadron collisions [10] and for the nuclear modification factor R p A [8], in case fluctuations become important in the range of LHC energies.…”
Section: Pomeron Loop Equationsmentioning
confidence: 99%
“…New evolution equations [5,6,7], which describe Pomeron loops, have been proposed to account for the above effects. Very recently possible effects of Pomeron loops on various observables [8,9,10] have been studied in case they become important in the range of collider energies.…”
Section: Introductionmentioning
confidence: 99%